The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1365-2052.2004.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Using mitochondrial nucleotide sequences to investigate diversity and genealogical relationships within common carp (Cyprinus carpio L.)

Abstract: Direct sequencing of mitochondrial DNA (mtDNA) D-loop (745 bp) and MTATPase6/MTATPase8 (857 bp) regions was used to investigate genetic variation within common carp and develop a global genealogy of common carp strains. The D-loop region was more variable than the MTATPase6/MTATPase8 region, but given the wide distribution of carp the overall levels of sequence divergence were low. Levels of haplotype diversity varied widely among countries with Chinese, Indonesian and Vietnamese carp showing the greatest dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…These authors attributed the loss of genetic variability to genetic drift due to small population sizes or to bottleneck effects, at the beginning or during the culture of populations. Similarly, Thai et al (2004) reported that a remarkable feature of European common carp samples is the low variation which suggests a history of founder effects and small effective population size, associated with translocation and domestication. However, it must also be stated that limited variation due to bottleneck effects and small effective population sizes is also frequent for a number of Greek freshwater fish populations (Apostolidis et al 1997;Imsiridou et al 1997;Triantafyllidis et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…These authors attributed the loss of genetic variability to genetic drift due to small population sizes or to bottleneck effects, at the beginning or during the culture of populations. Similarly, Thai et al (2004) reported that a remarkable feature of European common carp samples is the low variation which suggests a history of founder effects and small effective population size, associated with translocation and domestication. However, it must also be stated that limited variation due to bottleneck effects and small effective population sizes is also frequent for a number of Greek freshwater fish populations (Apostolidis et al 1997;Imsiridou et al 1997;Triantafyllidis et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Kottelat [6] distinguished the common cultured carp in South East Asia as a separate species, C. rubrofuscus, although this is disputed by Nguyen and Ngo [58] who considered this species to be quite rare. Using mtDNA analysis, Thai et al [16] found that Vietnamese and Indonesian carp strains are genetically distinct from European, Chinese and Japanese strains thereby supporting the Kottelat's taxonomy [6].…”
Section: Genetic Diversity Of Common Carpmentioning
confidence: 94%
“…Interestingly, the analysis with mtDNA showed that the Amur carp holds mtDNA haplotypes, one of those is very close to that of the European carp while another one is almost identical with that of the East Asian carp [16,50].…”
Section: Genetic Diversity Of Common Carpmentioning
confidence: 98%
See 2 more Smart Citations